Guidance for environmental footprint assessment of food products (Food-LCA) : Specification for external communicational purposes on the Finnish market - Heusala, Hannele; Lehtilä, Anniina; Hietala, Sanna; Katajajuuri, Juha-Matti; Leinonen, Ilkka; Lindfors, Kim; Silvenius, Frans; Tuomisto, Hanna; Usva, Kirsi (Luonnonvarakeskus, 2024)
Guidance for environmental footprint assessment of food products (Food-LCA) - Specification for external communicational purposes on the Finnish market is a national guidance based on Life Cycle Assessment (LCA). It is targeted for conducting voluntary environmental footprints assessments for food products. The guidance is based on the European Commission’s (EC) Product Environmental Footprint (PEF) method (EC 2021), but it aims to cover widely the whole food product category and it includes national specifications compared to the PEF. Therefore, this guidance is not fully corresponding with the PEF method. Food-LCA guidance aims to harmonize the LCA of food products’ environmental footprints in Finland, thereby promoting the comparability, reliability, and transparency of environmental footprints. This guidance has been prepared by researchers from the Natural Resources Institute Finland (Luke) as part of the LCAFoodPrint project (2021-2025). More information: https://www.luke.fi/en/projects/lcafoodprint. A wide group of professionals from the food sector including companies, ministries, research institutes, and other stakeholders were involved in commenting and development of this guidance.
Keywords: Life cycle assessment; Environmental footprint; Product Environmental Footprint; Food products